مقارنة تأثير البتاكسولول والتيمولول في علاج الزرق البدئي مفتوح الزاوية - كردغلي, نجوى; درويش, تيم; نورعلي شاهي, علي رضا (Latakia University Journal -Medical Sciences Series, 2019)
يهدف البحث لدراسة تأثير قطرة البتاكسولول0.5% و قطرة التيمولول %0.5 على انخفاض الضغط داخل العين , و تأثيراتهما على قياس متوسط ضغط الدم ,النبض, إفراز الدمع و الآثار الجانبية العينية. لقد شملت هذه الدراسة 28 مريضاً تم انتقاؤهم بشكل عشوائي من مجموعة المرضى المصابين بالزرق البدئي مفتوح الزاوية و المراجعين للعيادة العينية في مشفى الأسد الجامعي باللاذقية على امتداد العام 2009. وصف لكل مريض قطرة البتاكسولول0.5 % مرتين يومياً لمدة أسبوعين, تبعها أسبوع دون معالجة, ثم أسبوعين طبقت خلالها قطرة التيمولول 0.5 %. كان لكل من التيمولول والبتا كسولول تأثير خافض لضغط العين بـ 29% و23% على التوالي, والاختلاف كان هاماً إحصائياً (p<0.01). كل من الدوائين خفض ضغط الدم والنبض, ولكن الاختلاف لم يكن هاماً إحصائياً (p>0.1). التغيرات في إفراز الدمع لم تكن ملحوظة (p>0.5). الشكوى الأكثر انتشاراً كانت حرقة العين التي كانت أعلى بالبتاكسولول (64.2%) مقارنةً مع التيمولول (39.2%). العوارض الأخرى كانت تقريباً متشابهة في كلا الدوائين . The target of the study was comparing the effect of Betaxolol 0.5% and Timolol 0.5% eye drops, reducing IOP, as well as their effects on pulse rate, mean arterial pressure, tear secretion, and their ocular adverse effects. The study has included 28 randomly selected patients, suffering from primary open angle glaucoma, who sought medical advice in Ophthalmology clinic at Al-Asad hospital in Lattakia in 2009. Each patient received Betaxolol 0.5% twice daily for two weeks, followed by a week using no medication, and then two weeks receiving Timolol 0.5 % twice daily. At the end of every week, the effect of each drug on IOP, mean arterial blood pressure, pulse rate, tear secretion, and ocular symptoms were evaluated. Both Timolol and Betaxolol reduced IOP by 29% and 23% respectively, and the difference was significant (p<0.001). Likewise, both drugs reduced blood pressure, and pulse rate; yet the difference was not significant (p<0.1). On the other hand, changes in tear secretion were not significant (p<0.5). The most common complaint whith both drugs was eye burning which was higher with Betaxolol (64.2% vs. 39.2%), whereas, the prevalence of other symptoms were almost similar with the two drugs.